The Representation of Identity Crisis in Minari: A Critical Discourse Analysis - Ignatius Indra Kristianto; Aprilia Kristiana Wahyuni (LPPM Universitas Bumigora Mataram, 2022)
This study examines the representation of identity crisis in Minari, an American film depicting the life of Korean diasporas in the USA. This study employed Critical Discourse Analysis to analyze the identity crisis encountered by the main character and Korean and western cultural contact in the United States of America. The researchers analyzed the main protagonist using psychological perspectives to uncover unconsciousness in his decision-making to obtain the study's objectives. In this study, the main character of this film was Jacob, after undergoing the three stages of Greimas’ structural analysis. The main character displayed an identity crisis in discursive actions, non-discursive, and discourse materialization. Further analysis uncovered that immigration was the basis for the identity crisis in Minari. Moreover, the identity crisis was described in Jacob's roles in the diaspora process: the first child, husband, and father. Of the three roles, the circumstances experienced in the diaspora process made Jacob struggle with his identity. Fortunately, he overcame the identity crisis, which was symbolized by minari, a vegetable, as a symbol of perseverance in the film.